A model for psychiatric nurses to facilitate the mental health of women living with borderline personality disorder - Nompumelelo Ntshingila; Annie Temane; Marie Poggenpoel; Chris Myburgh (AOSIS, 2021)
Background: Borderline personality disorder (BPD) is characterised by emotional dysregulation, feelings of worthlessness, impulsivity, suicidality and poor relationships. As a result of the challenges in the treatment of women living with BPD and the lack of skills from the psychiatric nurse, there was a need to develop a model for psychiatric nurses to facilitate the mental health of women living with BPD. Objectives: To describe the process that was followed in developing, describing and evaluating a model that could be used as a framework of reference for psychiatric nurses to facilitate the mental health of women living with BPD. Method: A theory-generative, qualitative, exploratory, descriptive and contextual study design was used to develop the model. The central concept of the model was derived from a previous study: 'The experiences of women living with borderline personality disorder'. The process entailed the identification of the central concept and other essential criteria, the classification of the central concepts and describing the relationships between the concepts. Results: The central concept was identified as 'facilitation of self-empowerment' of women living with BPD. The concepts 'facilitation' and 'self-empowerment' were defined and classified. The identified and defined central concepts were placed into interrelated statements. The model to facilitate self-empowerment of women living with BPD was developed, described and evaluated. The model has not been implemented. Conclusion: The model provides a framework of reference for psychiatric nurses to facilitate self-empowerment of women living with BPD.